Artistic Negotiation of Emma and Lucy Annual Drama The Musical Jekyll & Hyde: A Performance Quadrilogue View - Untung, Rachel Mediana; Kusumaningtyas, Purwanti (Mudra Jurnal Seni Budaya, 2024)
The main focus is on the artistic aspects of the two female characters, Emma Carew and Lucy Harris in the production of “The Musical Jekyll & Hyde” by the Annual Drama team of Faculty of Language and Arts, Satya Wacana Christian University Salatiga, in 2023. The study focused on the process and artistic decision making within the context of management, musicology, dramaturgy, and literary studies. The study highlights how Emma and Lucy, are constructed in feminism artistic analysis in contemporary drama. The characters represented female with their domestic and private roles. Observation, interviews, documentation, and library studies were conducted to gather the data. Using performance centered approach, the study thoroughly observed the artistic decision process of the three actors of performance quadrilogue, namely the source, producer, and performer. As a college theater, all the artistic decision was made by the students. The four artistic elements of theater production, comprising the verbal text, song, movement, and scenary, portrayed the story’s setting in the 1800s in England. Emma’s verbal text depicted the English women of the elite with their domestic orientation. On the contrary, Lucy portrayed liberal English women. The four artistic elements in a theater production, referred to Broadway theater of the same title. This study positioned artistic elements as its study object instead of drama as a media of English learning. These two domains are discussed to sharpen on the construction of the female figure in the artistic perspective of feminist analysis. Post-production studies are also conducted to examine how students gain experience of an artistic decision-making process in producing a performance. It was conducted through the management’s delegating mechanism in the chart of the structured organization.